CONCEPT OF INTERACTION OF PRESCHOOL EDUCATION ORGANIZATION WITH FAMILY IN MODERN PSYCHOLOGIST- PEDAGOGICAL LITERATURE (UBS Scientific Bulletin, 2024)
In this article, the impact of education and upbringing in the family on the influence of different regional conditions has different effects on the development of children, the role of the family in the early stages of a child's life, the formation of parents' desire to cooperate with the employees of preschool education organizations, theoretical information and practical recommendations about the leading position of the family in the life of a child as the first educator of babies.